Overcoming chemoresistance in pancreatic cancer cells: role of the bitter taste receptor T2R10 - Stern, Louisa; Giese, Nathalia; Hackert, Thilo; Strobel, Oliver; Schirmacher, Peter; Felix, Klaus M.; Gaida, Matthias (Journal of cancer, 2018)
Bitter taste receptors (T2Rs) are G-protein coupled transmembrane proteins initially identified in the gustatory system as sensors for the taste of bitter. Recent evidence on expression of these receptors outside gustatory tissues suggested alternative functions, and there is growing interest of their potential role in cancer biology. In this study, we report for the first time, expression and functionality of the bitter receptor family member T2R10 in both human pancreatic ductal adenocarcinoma (PDAC) tissue and PDAC derived cell lines. Caffeine, a known ligand for T2R10, rendered the tumor cells more susceptible to two standard chemotherapeutics, Gemcitabine and 5-Fluoruracil. Knocking down T2R10 in the cell line BxPC-3 reduced the caffeine-induced effect. As possible underlying mechanism, we found that caffeine via triggering T2R10 inhibited Akt phosphorylation and subsequently downregulated expression of ABCG2, the so-called multi-drug resistance protein that participates in rendering cells resistant to a variety of chemotherapeutics. In conclusion, T2R10 is expressed in pancreatic cancer and it downmodulates the chemoresistance of the tumor cells.
Gesehen am 15.04.2020